A synopsis of Nimmo's Croton (Euphorbiaceae: Crotoneae) including an overlooked new species from India. Issue 4 (26th July 2021) - Dhabak, Maniruddin R.; Chaudhari, Rushabh B.; Bramhadande, Sneha P.; Nandikar, Mayur D.
Abstract: Graham's posthumous publication (Cat. Pl. Bombay, 1839) was completed by Joseph Nimmo, in addition to contributing several new species in it. Croton gibsonianus Nimmo and C. lawianus Nimmo (Euphorbiaceae) were part of this addition, and both were described based on Gibson's collection from adjoining localities in the Western India. As the diagnosis of the latter species was scant, it was subsequently interpreted in different genera viz. Dimorphocalyx, Trigonostemon and Tritaxis . Due to misinterpretation of the protologue and Gibson's Croton collection housed at K, the name C. lawianus was wrongly applied to C. gibsonianus by subsequent authors. This inadvertent application of name is corrected here and referred to the hitherto undescribed new species C. chakrabartyi . Our recent collection of C. gibsonianus has turned out to be a rediscovery after 170 years. The nomenclature, description, photographs, and distribution of C. gibsonianus are provided to avoid further taxonomic ambiguity.